Editor's Choice – Self-referral to the NHS Abdominal Aortic Aneurysm Screening Programme. Issue 3 (September 2016) - Meecham, L.; Jacomelli, J.; Pherwani, A.D.; Earnshaw, J.
Abstract : Introduction: The NHS Abdominal Aortic Screening Programme (NAAASP) invites men in their 65th year for screening, men over 65 may self-refer into the programme. Most studies have concentrated on those invited for screening, little is known about the self-referral group. Our aim was to provide a descriptive analysis of the men who self refer to NAAASP for screening. Method: Information concerning basic demographic details and ultrasound results were recorded on the AAA SMaRT database. During nurse assessment data collected included smoking status, blood pressure, height, weight, and aspirin and statin therapy. Statistical analysis was performed using SPSS ® 20. Results: A total of 58, 999 men have self-referred to the NAAASP since its inception. The mean age at self-referral was 73 (47–100). The mean aortic diameter was 1.9 cm (0.8–12.1). Increased self-referral rates were observed following organised publicity. The incidence of AAA was 4.1% ( n = 2438) compared with 1.4% in the invited cohort (age 65 years), of these 7.6% ( n = 186) were >5.5 cm. Of the 186, 152 (81.7%) underwent surgery, of which 55.3% ( n = 84) underwent EVAR. The 30-day mortality in the men treated electively was 0%. The mean time from referral to surgery was 69 (2–361) days, with 57.9% ( n = 88) being treated within 8 weeks of detection. Conclusion: Self-referral has yielded higher detection rates than the invited cohort, more than justifying its cost. Now that NAAASP is fully operational it is important to continue media campaigns and publicity to target the "at-risk" men over 65 who would otherwise miss the benefits of AAA screening. Some key areas still need to be addressed.